Household debt and consumption inequality: The Spanish case - Gonzalo Paz Pardo; José Manuel Sánchez Santos (Economies, 2014)
The aim of this paper is twofold. On the one hand, we attempt to find out whether Spanish households took part in a process of substituting loans for wages during the period before the beginning of the current economic crisis. On the other hand, we try to identify the consequences of such process in the evolution of income and consumption inequalities. The theoretical framework to deal with the above mentioned issues is provided by a review of the economic literature on the determinants of consumer behaviour, namely, on consumption, saving and debt. The empirical study consists of a descriptive analysis, which is focused on two fields. First, we analyze the evolution of consumer credit (both, in aggregate and by income groups) and the savings rates. Second, we compare the values and temporal evolution of income and consumption inequalities. The period under study ranges from 2000 to 2008. Our analysis provides some empirical evidence that supports the hypothesis that financial conditions led to significant effects on the distribution of consumption. This influence is especially significant in the case of consumption inequalities. These inequalities were lower than income inequalities and were kept "artificially" low and stable during the whole period.
Keywords: 330; financial conditions; household indebtedness; consumer credit; income distribution; consumption inequalities